Effective stabilization of curcumin by association to plasma proteins human serum albumin and fibrinogen - Leung, Mandy H M (Langmuir : the ACS journal of surfaces and colloids, 2009)
The use of curcumin as an effective wound healing agent is of significant interest currently. It is well established that curcumin undergoes rapid degradation in physiological buffer by hydrolysis. The means by which curcumin is stabilized at the wound site to enable healing is poorly understood because blood plasma is composed of approximately 92% water. Plasma proteins, which constitute the remaining 6-8%, has been shown to stabilize curcumin. It is, however, still unclear which proteins are responsible for this phenomenon. In this study, the effects of major plasma proteins, which include human serum albumin (HSA), fibrinogen, immunoglobulin G (IgG), and transferrin, on stabilizing curcumin are investigated. In particular, we investigate their effects on the hydrolysis of curcumin at pH 7.4. In the presence of both transferrin and IgG, curcumin continues to undergo rapid hydrolysis but this reaction is suppressed by the presence of either HSA or fibrinogen with an impressive yield of approximately 95%. Furthermore, the binding constants of curcumin to HSA and fibrinogen are on the order of 10(4) and 10(5) M(-1), respectively. The binding constants of transferrin and IgG, however, are at least 1 order of magnitude less than those of HSA and fibrinogen. The results support that strong binding occurs at the hydrophobic moieties of HSA and fibrinogen, excluding water access. Therefore, strong interactions with HSA and fibrinogen inhibit hydrolysis of curcumin and in turn lead to effective suppression of degradation